The Applicability Evaluation of Multisource Precipitation Data for Runoff Simulation in a Typical Basin on the Tianshan Mountains - WANG Wenyu; LIU Gang; WANG Xiaoyan; PANG Liling; FENG Tongfei; GU Huanghe (Shuitu Baochi Xuebao)
[Objective] To explore the differences in precipitation characteristics for multisource precipitation products and their applicability for runoff simulation in an alpine basin on the Tianshan Mountains. [Methods] A comparative analysis of the spatiotemporal characteristics of precipitation was conducted in the upper reaches of the Manas River Basin, based on the datasets CN05.1, GPM, AIMERG, CMFD and ERA5. Subsequently, the accuracy of different products was evaluated based on observed precipitation, and their applicabilities for runoff simulation were assessed by means of HBV hydrological model. [Results] The spatial pattern for all the precipitation products was characterized by a first increase and then a decrease from the north to south, whereas only AIMERG and CMFD were able to display higher precipitation in the glacier area. Consistent seasonal variation were detected, but large differences in summer precipitation were shown. In summer, ERA5 was twice as much as CN05.1, and GPM was lower than the other precipitation products. GPM underestimated the monthly precipitation, especially in winter and spring (64%—76%). While the monthly precipitation was overestimated by CMFD, ERA5 and AIMERG. The overestimation of ERA5 was the most serious, especially in summer and autumn (134%—206%), and CMFD slightly overestimated the monthly precipitation. AIMERG had a higher correlation with the observed monthly precipitation and greater critical success index in both rainy season and the non-rainy season. AIMERG, CMFD and CN05.1 had the greatest ability to reproduce daily runoff, with a higher NSE (0.81—0.82) and lower relative error (<6%). Moreover, the former two products showed a better performance in reproducing extreme runoff when compared with CN05.1. [Conclusion] AIMERG and CMFD show great potential in runoff simulation of the upper Manas River. The results can serve as data references for runoff simulation and soil erosion prevention research in the Tianshan region, where meteorological data are limited.